HUBUNGAN KOMPETENSI KEPRIBADIAN DAN INTEGRITAS DENGAN KINERJA GURU SMP SE-KECAMATAN DUMAI KOTA - Astuti S; Isjoni Isjoni; Daviq Chairilsyah (Universitas Riau, 2023)
This study aims to determine the relationship between the variables (1) personality competence with teacher performance, (2) integrity with teacher performance, (3) personality competence and integrity together on teacher performance. The research respondents were all junior high school teachers in Dumai Kota sub-district totaling 91 people obtained by simple random sampling technique. The sample in this study amounted to 74 teachers. Data was collected through the distribution of questionnaires as a research instrument. The data analysis used is descriptive analysis, inferential statistical analysis and hypothesis testing. The instrument reliability coefficient was calculated using the Cronbach alpha formula. Partially, the results showed that there was a positive relationship between personality competence and teacher performance of 0.681, and there was a positive relationship between integrity and teacher performance of 0.643. Meanwhile, together there is a positive relationship between personality competence and integrity on teacher performance of 0.717